2014
DOI: 10.1002/wsb.469
|View full text |Cite
|
Sign up to set email alerts
|

Causes of mortality in eagles submitted to the National Wildlife Health Center 1975-2013

Abstract: We summarized the cause of death for 2,980 bald eagles (Haliaeetus leucocephalus) and 1,427 golden eagles (Aquila chrysaetos) submitted to the National Wildlife Health Center in Madison, Wisconsin, USA, for diagnosis between 1975 and the beginning of 2013. We compared the proportion of eagles with a primary diagnosis as electrocuted, emaciated, traumatized, shot or trapped, diseased, poisoned, other, and undetermined among the 4 migratory bird flyways of the United States (Atlantic, Mississippi, Central, and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
76
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 26 publications
1
76
1
1
Order By: Relevance
“…As a proportion of the total number of bald eagles examined at the NWHC, the frequency of those diagnosed with lead poisoning increased in the U.S. after implementation of the 1991 restrictions on hunting waterfowl with lead shot (Russell and Franson 2014). The largest increase, from 6 % before 1991 to 30 % after 1991 occurred in the Pacific flyway (Russell and Franson 2014). No increase in lead poisoning was detected in golden eagles, but the sample size for that species was much smaller (Russell and Franson 2014).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…As a proportion of the total number of bald eagles examined at the NWHC, the frequency of those diagnosed with lead poisoning increased in the U.S. after implementation of the 1991 restrictions on hunting waterfowl with lead shot (Russell and Franson 2014). The largest increase, from 6 % before 1991 to 30 % after 1991 occurred in the Pacific flyway (Russell and Franson 2014). No increase in lead poisoning was detected in golden eagles, but the sample size for that species was much smaller (Russell and Franson 2014).…”
Section: Introductionmentioning
confidence: 93%
“…In that report, lead toxicosis was the most frequently diagnosed poisoning in both species, comprising 63.5 % of all poisonings in bald eagles and 58.1 % in golden eagles. As a proportion of the total number of bald eagles examined at the NWHC, the frequency of those diagnosed with lead poisoning increased in the U.S. after implementation of the 1991 restrictions on hunting waterfowl with lead shot (Russell and Franson 2014). The largest increase, from 6 % before 1991 to 30 % after 1991 occurred in the Pacific flyway (Russell and Franson 2014).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Passive surveillance strategies such as those used here have limitations, particularly when interpreting temporal trends when efforts to detect specimens are poorly documented or diagnostic effort is inconsistent (Russel and Franson 2014). In our case, animals were consistently examined by the same group by using similar techniques throughout the study, which should decrease variability.…”
Section: Discussionmentioning
confidence: 99%
“…Most recorded deaths are anthropogenic, including shooting, electrocution, and lead poisoning (Russell and Franson 2014;USFWS 2016a). Recent reviews concluded that U.S. golden eagle populations are either stable or slowly declining (USFWS 2016a).…”
Section: Introductionmentioning
confidence: 99%